Onset of major Pleistocene glaciations in the Alps - G. Muttoni; C. Carcano; E. Garzanti; M. Ghielmi; A. Piccin; R. Pini; S. Rogledi; D. Sciunnach (Geology, 2003)
During maximum Pleistocene glacial expansions, the Alpine ice cap invaded the Central Europe uplands and Italian Southalpine foothills. Periglacial basins, such as the Po River Basin, are natural collectors of sediments that record the past biological and climatic changes that involve the waxing and waning of major ice caps. In a 200-m-long core from the central Po Plain, stratigraphic evidence for one such major glacial pulse of the nearby Alpine ice cap is recorded by a sequence boundary, termed the R surface, associated with a drastic reorganization of vegetational, fluvial, and Alpine drainage patterns. The R surface, seismically traceable across the Po Plain subsurface, was constrained magneto-stratigraphically to the first prominent Pleistocene glacio-eustatic lowstand of marine isotope stage (MIS) 22 at 0.87 Ma. MIS 22 corresponds to the end of the Mid-Pleistocene Revolution, a marked reorganization of Northern Hemisphere glaciation pattern that took place in the late early Pleistocene. We suggest that the R surface formed at Mid-Pleistocene Revolution-MIS 22 time, during the onset of the first major Pleistocene glaciation in the Alps.